Digital volume correlation and micro-CT: An in-vitro technique for measuring full-field interface micromotion around polyethylene implants. Issue 12 (18th September 2015) - Sukjamsri, Chamaiporn; Geraldes, Diogo M.; Gregory, Thomas; Ahmed, Farah; Hollis, David; Schenk, Samuel; Amis, Andrew; Emery, Roger; Hansen, Ulrich
Abstract: Micromotion around implants is commonly measured using displacement-sensor techniques. Due to the limitations of these techniques, an alternative approach (DVC-μCT) using digital volume correlation (DVC) and micro-CT (μCT) was developed in this study. The validation consisted of evaluating DVC-μCT based micromotion against known micromotions (40, 100 and 150 μm) in a simplified experiment. Subsequently, a more clinically realistic experiment in which a glenoid component was implanted into a porcine scapula was carried out and the DVC-μCT measurements during a single load cycle (duration 20 min due to scanning time) was correlated with the manual tracking of micromotion at 12 discrete points across the implant interface. In this same experiment the full-field DVC-μCT micromotion was compared to the full-field micromotion predicted by a parallel finite element analysis (FEA). It was found that DVC-μCT micromotion matched the known micromotion of the simplified experiment (average/peak error=1.4/1.7 μm, regression line slope=0.999) and correlated with the micromotion at the 12 points tracked manually during the realistic experiment ( R 2 =0.96). The DVC-μCT full-field micromotion matched the pattern of the full-field FEA predicted micromotion. This study showed that the DVC-μCT technique provides sensible estimates of micromotion. The main advantages of this technique are that it does not damage important parts of the specimen to gain access to the bone–implant interface, and it provides a full-field evaluation of micromotion as opposed to the micromotion at just a few discrete points. In conclusion the DVC-μCT technique provides a useful tool for investigations of micromotion around plastic implants.